BioGlue and E‐Vita Open NEO graft oozing: Long‐term solution or band aid?. Issue 3 (16th December 2021) - Jubouri, Matti; Abdelhaliem, Amr
Abstract: Background: The introduction of the single‐step total arch replacement (TAR) with frozen elephant trunk (FET) has revolutionised the field of aortic surgery. TAR is indicated when the aortic arch is involved in aortic pathologies such as Type A aortic dissection and thoracic aortic aneurysms. Several FET devices are available commercially for global use, and example is the E‐Vita Open NEO hybrid prosthesis (HP) developed by CryoLife‐JOTEC. Unlike other FET devices available, this HP in particular features a design that puts it at a disadvantage as it does not incorporate gelatine or collagen in its structure, which makes it permeable to blood. Several studies have reported incidence of post‐anastomotic blood oozing through the E‐Vita Open NEO right after weaning from cardiopulmonary bypass. Aims: This commentary aims to discuss the recent study by Tan et al. which investigated E‐Vita NEO device oozing as well as the implications of using BioGlue to overcome this serious complications. Methods: We carried out a literature search on multiple electronic databases including PUBMED and Scopus in order to collate research evidence on E‐Vita NEO device oozing, BioGlue health risks, and other commercially available and globally used FET devices such as Thoraflex Hybrid. Results: It is proven fact that the E‐Vita NEO excessively oozes blood, and while BioGlue is a safe and effective agent when used in small amounts, the amount needed to coat the E‐Vita Open NEO and achieve haemostasis exceeds this by a wide margin which poses patients to great potential health risks. The Thoraflex Hybrid Prosthesis developed by Terumo Aortic is a commercially available and globally used FET device with long‐standing favourable outcomes. Discussion: Tan et al. recently conducted an interesting study which proved that the E‐Vita NEO HP does excessively ooze blood and tackled the issue of pre‐emptive BioGlue use to tackle this complication as suggested by Ho et al. This leads on to the main question, is the use of BioGlue with E‐Vita Open NEO to overcome oozing a long‐term sustainable solution or is it merely a band aid? Conclusion: In the face of fierce commercial competition, the choice of design and material of the E‐Vita Open NEO HP would benefit from reconsideration.